Penerapan Terapi Musik Klasik Untuk Meningkatkan Fungsi Kognitif Pada Lansia Dengan Demensia di Keluarga Wilayah Binaan Puskesmas Sekaran Semarang - Novita Wulan Sari; Margiyati Margiyati (Pusat Riset dan Inovasi Nasional, 2024)
Dementia or senility is an aging process so it is considered a normal thing and if dementia is not prevented or treated it will have an impact such as a decrease in cognitive function. Cognitive function is mental and intellectual abilities and memory. Cognitive function ability was measured using the MMSE (Mini Mental State Examination) questionnaire which consisted of 11 questions. Efforts to improve cognitive function one of them with classical music therapy. This case study aims to describe the application of classical music therapy to improve cognitive function in the elderly at the Sekaran Health Center in Semarang. This case study uses a type of case study with a descriptive approach. The subjects of this case study used 2 people with inclusion criteria: age between 60-74 years, able to communicate well, elderly with mild dementia (MMSE score 24-30) and moderate (probable) MMSE score 17-23, elderly who are cooperative and can read and write, the elderly who are not hearing impaired. This case study was conducted 4 meetings over 2 weeks. The results of this case study showed an increase in cognitive function felt by both subjects. Subject I from a score of 22 (probable cognitive disorder) to 28 (normal). Subject II from a score of 19 (probable cognitive disorder) to 25 (normal). Classical music therapy in conclusion can improve the cognitive function of elderly people with dementia and is recommended as an effective therapy application in improving cognitive function.